The Microcirculatiory Changes of the Optic Nerve Disc in Patients with Normal Tension Glaucoma in Comparison High Tension Glaucoma - A. Sh. Zagidullina; A. I. Arslanova; V. U. Galimova; A. A. Aleksandrov (Oftalʹmologiâ)
Normal tension glaucoma (NTG) is one of the difficult-to-diagnose clinical forms of primary open-angle glaucoma (POAG). One of the important links in the pathogenesis of this pathology is a violation of the blood supply to the optic nerve and retina.Purpose. Comparitive study using optical coherence tomography with angiography (OCTA), indicators of vessel density of the optic nerve head (ONH) in patients with newly diagnosed NTG and hypertensive form of POAG. The material was based on the data of 65 patients (65 eyes) with newly diagnosed NTG, 88 patients (88 eyes) with a hypertensive form of POAG and 50 healthy people without glaucoma (50 eyes) aged 45 to 65 years at the Eye Microsurgery Department in Hospital 8 (Ufa). All subjects underwent an ophthalmological examination, including OCTA of the optic nerve head with measurement of vessel density using the Angio Disc 4.5×4.5 mm protocol on the Optovue XR Avanti device with the AngioVue function (Optovue, USA). According to the results of the study, in patients with the initial stage of NTG, a decrease in the vessel density of the ONH was revealed in comparison with healthy individuals. In the advanced stage NTG the vessel density of the peripapillary region was reduced in all sectors of the ONH and correlated with the thickness of the RNFL in the upper sector (r = 0.404, p < 0.05). In patients with POAG, compared with NTG, more pronounced changes in the microcirculation of the ONH were observed in both stages of the disease. The vessel density of the peripapillary region correlated with the thickness of the retina in the upper sector at the early stage (r = 0.324, p < 0.05), in the lower sector — in stages I and II of the disease (r = 0.322, p < 0.05 and r = 0.316, p < 0.05, respectively).Conclusion. The OCTA of the ONH makes possible to detect microcirculatory changes at an early stage of the disease in patients with the hypertensive form of primary open-angle glaucoma and in patients with normal tension glaucoma.